2022
DOI: 10.1371/journal.pone.0268789
|View full text |Cite
|
Sign up to set email alerts
|

Plain language summaries: A systematic review of theory, guidelines and empirical research

Abstract: Plain language summaries (PLSs) have been introduced to communicate research in an understandable way to a nonexpert audience. Guidelines for writing PLSs have been developed and empirical research on PLSs has been conducted, but terminology and research approaches in this comparatively young field vary considerably. This prompted us to review the current state of the art of the theoretical and empirical literature on PLSs. The two main objectives of this review were to develop a conceptual framework for PLS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…Yet, while some relevant studies on the subject focus on the benefits in terms of costs and time for resorting to plain language like Kimble (2012), Lobban et al (2021) and Stoll et al (2022), few researchers have demonstrated the preference for plain language within the legal profession. For instance, amongst the first studies on this topic was the research conducted by Adler (2004) whereby some clients were provided with a legal advice and they were asked questions about their understanding of the content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet, while some relevant studies on the subject focus on the benefits in terms of costs and time for resorting to plain language like Kimble (2012), Lobban et al (2021) and Stoll et al (2022), few researchers have demonstrated the preference for plain language within the legal profession. For instance, amongst the first studies on this topic was the research conducted by Adler (2004) whereby some clients were provided with a legal advice and they were asked questions about their understanding of the content.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A physician may be interested in mode of action relative to therapeutic alternatives to select optimal therapy, a pharmacist focused on drug interactions to ensure safety, an infusion nurse ensuring the correct gauge needles are used with specific medications. For patients and caregivers, the widespread adoption of plain language summaries (PLS) affords an opportunity to communicate more effectively with this group of stakeholders [ 6 ]. What a PLS looks like is only constrained by limited thinking—they can take written, spoken, and visual forms in any channel, medium or format that that best meets patient needs.…”
Section: Medical Affairs and Communication Of Informationmentioning
confidence: 99%
“…Specifically, PERbites's three main goals are to (1) help researchers and educators keep up with recent DBER work; (2) lower barriers around understanding DBER papers; (3) expose readers to new teaching and research methods, so that they can apply them in their work. These goals are broadly aligned with common aims of plain language summaries according a recent review [16] and what readers of evidence summaries and blog posts care about [17]. Based on the authors' estimation, around 40% of the posts to date advance goal 3 by exposing readers to new teaching and research methods, while the remaining posts cover 'pure research', advancing the goal of helping researchers and educators keep up with DBER.…”
Section: About Perbitesmentioning
confidence: 99%